Wastra Sebagai Media Edukasi Ekologis Dalam Mendukung Tujuan Pembangunan Berkelanjutan di Kota Samarinda - Kadek Dristiana Dwivayani; Harry Isra Muhammad; Andi Aqil Ajrun Adhim; Yaasiina Nur Laila Aprilia; Alyda Khairunnisa (Varied Knowledge Journal, 2026)
Wastra refers to Indonesian traditional textiles, such as batik and Samarinda woven fabrics, which possess historical, aesthetic, and economic value as part of local cultural heritage. Amid increasing environmental issues, particularly water pollution caused by production activities, wastra has the potential not only as a cultural product but also as a communication medium for conveying sustainability values. This study aims to analyze the role of wastra as a medium for ecological education in supporting the achievement of the Sustainable Development Goals (SDGs) in Samarinda City, and to understand how symbolic interaction processes shape ecological awareness and practices in wastra production.This research employs a qualitative approach with a case study method focusing on the practice of Samarinda weaving in Kampung Tenun. Data were collected through in-depth interviews with artisans, the Joint Business Group (KUB) Putri Mahakam, batik activists, consumers, and the Department of Industry, Trade, Cooperatives, and SMEs of Samarinda City. The analysis was conducted using George Herbert Mead’s symbolic interactionism approach as further developed by Herbert Blumer.The findings indicate that the function of wastra as a medium for ecological education has not yet been integrated into promotional communication, such as exhibitions and tourism activities, resulting in only partial or fragmented contributions to the SDGs, particularly SDGs 8, 11, and 12. This study also contributes theoretically through the integration of symbolic interactionism, environmental communication, and the concept of communication fragmentation within the context of local culture.